Preliminary results on correlation in daily f0F2 and M(3000)F2 variations - Y Nissopoulos; K. Barbatsi; B. Zolesi; T. D. Xenos; S. S. Kouris (Annals of Geophysics, 1994)
A statistical analysis of the hourly daily values of the factor M(3000)F2 and the F2-layer critical frequency f0F2 is carried out first for each hour of the day through-out a given month of a given year at a given station (hour-to-hour variation) and then for each day of a given month and year at a given station (day-to-day variation). This analysis shows that these ionospheric characteristics are poorly correlated. It is concluded that the daily values of the first characteristic cannot be estimated from the second by using a simple linear equation.